PRODUCTION OF HYBRID SEEDS OF THE VEGETABLE MARROW AT FREE POLLINATION - S. V. Kuzmin; A. V. Medvedev; A. F. Bukharov (Овощи России)
The purpose of this work performed in 2015-2017 on seedgrowing crops of the Crimean OSS VIR was receiving hybrid seeds of a vegetable marrow at free pollination and check of their quality by method of soil control. At laying of seed-growing crops, carrying out variety cleanings,, inspections and approbation were guided by the Instruction for approbation of seedgrowing crops of vegetable, melon cultures, fodder root crops and fodder cabbage (2008). The vegetable marrow with a high saturation pistillate flowers of Bl12, Su4 and Ar3 were used as maternal lines. Double processing by solution of an etrel was carried out to early phases of development of plants them. Use of this growth regulator has influenced blossoming of plants - in the lower knots men's flowers weren't formed, purely women's blossoming for the term of 14-17 days, sufficient for setting of seed fruits was observed. Control of blossoming of maternal forms was exercised by systematic inspections of plants on a floor. We have conducted three multiple examination. The first - before blossoming of maternal plants, in a budding phase when it is already possible to distinguish a sex of flowers, the second – in a phase of the beginning of blossoming. The third examination was conducted for definition of the beginning of blossoming of male flowers on plants of the maternal line. Timely carrying out inspections and variety cleanings, promotes receiving qualitative hybrid material. When carrying out soil control the high hybridism of seed material is revealed: F1 Bl12 x D1 - 95,3 %; F1 Su4 x D1 - 95,7 %; F1 Ar3 x D1 - 96,0 %. The results indicate that of the carried-out work, at free pollination of maternal and fatherly forms, vegetable marrow seeds with a high hybridism are received. Conducting the trial testing of new hybrids showed their high economic value. In comparison with the standard of Belogor F1, their total yield is higher by 16.7-25.7%, and the early yield by 10.5-27.7%. The introduction of new vegetable marrow hybrids in production is cost-effective and in demand.